Gliclazide Prevents 5-FU-Induced Oral Mucositis by Reducing Oxidative Stress, Inflammation, and P-Selectin Adhesion Molecules - Mafra, Cristiane Assunção da Costa Cunha; Vasconcelos, Roseane Carvalho; Medeiros, Caroline Addison Carvalho Xavier de; Leitão, Renata Ferreira de Carvalho; Brito, Gerly Anne de Castro; Costa, Deiziane Viana da Silva; Guerra, Gerlane Coelho Bernardo; Araújo, Raimundo Fernandes de; Medeiros, Aldo Cunha; Araújo, Aurigena Antunes de (Frontiers in Physiology, 2019)
Oral mucositis (OM) is one of the main side effects of the head and neck cancer treatment, particularly radiotherapy and/or chemotherapy. OM is characterised by ulcers, erythema, dysphagia, xerostomia and increased susceptibility to opportunistic infections. In the perspective of finding pharmacological therapies to prevent inflammation and ulceration of OM, the investigation of the pleiotropic effect of commercial drugs is needed, among them gliclazide, an antidiabetic drug. This study aimed to evaluate the effect of gliclazide in an experimental OM model induced by 5-fluorouracil. Male hamsters were pre-treated with oral gliclazide (1, 5, or 10 mg/kg) for ten days. Cheek pouch samples were subjected to histopathological and immunohistochemical analysis (COX2, iNOS, MMP-2, NFκB P65, GPx) and imunofluorescence (P-selectin). IL-1β and TNF-α levels, Myeloperoxidase activity (MPO) and malondialdehyde (MDA) levels were investigated by ultraviolet-visible spectroscopy analysis. NFκB NLS P50 protein levels were analysed by western blotting. The group treated with gliclazide at a dose of 10mg/kg showed presence of erythema, no evidence of erosion, and absence of mucosal ulceration with a score of 1 (1-2) (p<0.01). Histopathological data for the group treated with gliclazide 10mg/kg showed re-epithelialization, discrete mononuclear inflammatory infiltrate and absence of hemorrhage, edema, ulcers and abscesses with a score of 1 (1-1), (p<0.01). Treatment with gliclazide 10 mg/kg reduced MPO activity (p<0.001), MDA levels (p<0.001) and NFκB NLS P50 (p<0.05) protein levels, resulting in low immunostaining to Cox-2, iNOS (p<0.05), NFκB P65 (p<0.05), and negative immunoreaction to MMP-2 (p<0.001). However, it appeared that for Gpx1, the staining was restored in the GLI 10-FUT group compared with 5FUT/saline (p <0.05). Immunofluorescence revealed decreased levels of P-selectin (p<0.001) after treatment with gliclazide 10mg/kg (p<0.05). In summary, gliclazide accelerated mucosal recovery and reduced oxidative stress and inflammation in the 5-FU-induced OM in hamsters.